Nest-box occupancy by neotropical raptors in a native forest of Central Argentina - Liébana, María Soledad (2013)
Breeding populations of raptors are sometimes limited by nest-site availability and the use of nest boxes to bolster such populations is widespread. In the neotropical forest, little is known about the ecology of cavity-nesting raptors and their use of nest boxes. Here we examine occupancy patterns of nest boxes by five raptor species during eight years in a semiarid forest of central Argentina: the American Kestrel (Falco sparverius), the Spot-winged Falconet (Spiziapteryx circumcincta), the Tropical Screech-Owl (Megascops choliba), the Barn Owl (Tyto alba), and the Ferruginous Pygmy-Owl (Glaucidium brasilianum). We analyze the influence of vegetation type on nest-box selection, report cases of nest usurpation, and present information on the breeding rates of some of these species. The raptor species showed a marked selection for nest boxes surrounded by grassland, where hunting success may be higher, and avoided those nest boxes placed in habitats dominated by dense shrublands. We observed two cases of nest usurpation (i.e., a species takes over active nests of another species for breeding purposes), in which two different boxes were occupied almost simultaneously by the Ferruginous Pygmy-Owl and the American Kestrel.